Polyarylamide modified boron nitride-epoxy resin composite material and preparation method thereof
By aminating the surface of hexagonal nanoboronitride and modifying it with hyperbranched polyaramide, and preparing composite materials in combination with epoxy resin, the problem of poor thermal conductivity of epoxy resin is solved, and excellent thermal conductivity and efficient heat dissipation effect are achieved.
Patent Information
- Application Number
- CN202411759700.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the field of electronic packaging, epoxy resins are difficult to adapt to the rapid development of electronic integration technology due to their poor thermal conductivity and low heat dissipation performance.
By introducing an amino treatment to the surface of hexagonal nanoboronitride and modifying it with hyperbranched polyaramide, polyaramide modified boron nitride is formed, and a composite material is prepared in combination with epoxy resin.
It improves the thermal conductivity of the composite material, reduces the agglomeration phenomenon of nanoboronitride, enhances compatibility and dispersion, and thus improves the overall performance of the material.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy resins, in particular to a polyaromatic amide modified boron nitride-epoxy resin composite material and a preparation method thereof. Background Art
[0002] With the development of economy, electronic integration technology and electronic assembly technology are developing rapidly, and the requirements for high voltage in the field of power insulation are getting higher and higher. This requires the size of components and circuits to gradually shrink and become thinner, while the operating frequency is increased. This will largely lead to a rapid accumulation of heat during the working process and an increase in the working temperature. In order to ensure that electronic components can continue to work stably and efficiently, it is necessary to prevent the working temperature from continuing to increase. The key lies in whether it can dissipate heat quickly during the continuous heating process, which requires the development of high thermal conductivity materials.
[0003] Epoxy resin is a common material used in the field of electronic packaging. It is widely used because of its low price and good insulation performance. However, in the era of rapid development of electronic integration technology, epoxy resin is difficult to adapt to the rapid development due to its poor thermal conductivity and low heat dissipation performance. There are many methods to improve the thermal conductivity of epoxy resin, usually including intrinsic type and filled type. The efficient method is usually to add inorganic fillers with high thermal conductivity, common ones include boron nitride, silicon carbide, aluminum oxide, etc. These fillers have small particle size and large specific surface area, and excellent thermal conductivity, thermal stability, corrosion resistance and other performance. However, when using this type of filler for surface modification, due to the unstable thermodynamic state, agglomeration may occur to a large extent, reducing the compatibility and dispersibility, thereby affecting the overall performance of the material. In order to reduce this defect, the filler can be modified accordingly, and groups can be introduced. The introduction of substances such as hyperbranched polyarylamide, the structure of the hyperbranched polymer is highly branched, and it contains a large number of terminal functional groups, which can improve the reactivity of the polymer and greatly improve the overall performance of the filler, so that the polymer material can have better thermal conductivity.
[0004] In view of the deficiencies in the prior art, the present invention provides a polyaromatic amide modified boron nitride-epoxy resin composite material and a preparation method, which solves the problem of poor thermal conductivity and heat dissipation of epoxy resin and exhibits excellent thermal conductivity.
[0005] To achieve the above object, the present invention provides the following technical solution: a polyaromatic amide modified boron nitride-epoxy resin composite material, wherein the preparation method of the polyaromatic amide modified boron nitride-epoxy resin composite material comprises the following steps: (1) adding sodium hydroxide solution and hexagonal nano-boron nitride into a beaker for hydroxylation to obtain hydroxylated nano-boron nitride, then adding the hydroxylated nano-boron nitride into a hydrochloric acid solution, mixing evenly, adding elemental iron, and then adding 4-diazodiphenylamine sulfate, stirring and reacting, performing a diazonium salt reaction, and obtaining surface amino-treated nano-boron nitride; (2) Adding N-methylpyrrolidone to the reactor, then adding amino-modified nano boron nitride and 3,5-diaminobenzoic acid, stirring and mixing evenly, ultrasonically dispersing, then adding a mixed solution of pyridine and triphenylphosphine, and then adding lithium chloride, reacting in a nitrogen atmosphere, and after the reaction is completed, cooling, filtering, washing, and drying to obtain polyaromatic amide modified boron nitride; (3) Add acetone solvent to a beaker, then add polyaromatic amide modified boron nitride, disperse by ultrasonic stirring, then add epoxy resin, azodicarbonamide and diethylenetriamine, stir and react. After the reaction is completed, evaporate the solvent in a water bath to obtain a polyaromatic amide modified boron nitride-epoxy resin composite material.
[0006] Preferably, in step (1), the mass ratio of hexagonal nano-boron nitride to 4-diazodiphenylamine sulfate is 100:450-500.
[0007] Preferably, in step (1), the temperature of the diazonium salt reaction is 25-35° C., and the time of the diazonium salt reaction is 30-90 min.
[0008] Preferably, in step (2), the mass ratio of the amino-modified nano-boron nitride, 3,5-diaminobenzoic acid, pyridine, triphenylphosphine and lithium chloride is 100:60-80:90-110:320-350:20-30.
[0009] Preferably, in step (2), the reaction temperature in the nitrogen atmosphere is 120-150° C., and the reaction time in the nitrogen atmosphere is 12-18 h.
[0010] Preferably, in step (3), the mass ratio of polyaromatic amide modified boron nitride, epoxy resin, azodicarbonamide and diethylenetriamine is 15-25:100:2-8:1-3.
[0011] Preferably, the stirring and mixing reaction temperature in step (3) is 100-120° C., and the reaction time is 6-12 h.
[0012] Compared with the prior art, the present invention has the following chemical mechanisms and beneficial technical effects: The polyaromatic amide modified boron nitride-epoxy resin composite material comprises the following steps: firstly, hexagonal nano boron nitride is treated with a strong base to obtain hydroxylated nano boron nitride; in a hydrochloric acid and elemental iron system, the hydroxyl group generates oxygen free radicals, which react with the diazo group of 4-diazodiphenylamine sulfate to obtain amino nano boron nitride; the introduced amino group first undergoes an esterification reaction with 3,5-diaminobenzoic acid, and then undergoes a polymerization reaction with a 3,5-diaminobenzoic acid monomer to obtain the polyaromatic amide modified boron nitride; lithium ions in lithium chloride undergo a complexation reaction with oxygen atoms on the amide group, thereby increasing the intermolecular force; since the polyaromatic amide modified boron nitride has good compatibility with the epoxy resin, and the terminal amino group in the polyaromatic amide can undergo a ring-opening reaction with the epoxy group of the epoxy resin, the nano boron nitride is organically combined with the epoxy resin under the bridging action of the polyaromatic amide to obtain the polyaromatic amide modified boron nitride-epoxy resin composite material.
[0013] The polyaromatic amide modified boron nitride-epoxy resin composite material has a large number of terminal functional groups on the surface of the hyperbranched polyaromatic amide, which can be well grafted on the surface of the amino-modified nano boron nitride, has high solubility and low solution viscosity, reduces the agglomeration phenomenon of the nano boron nitride due to its own thermodynamic instability, improves compatibility and dispersibility to a great extent, improves the organic-inorganic interface strength, and thus improves its reaction activity. The covalent bonds formed between the large number of amino groups on the surface and the epoxy resin during the curing process participate in the cross-linking curing reaction, thereby reducing the free volume of the composite material, improving the cross-linking density, and effectively reducing the interface thermal resistance between the filler and the epoxy resin. The nano boron nitride has ultra-high resistivity, reduced agglomeration, and modified fillers, so that the epoxy resin composite material exhibits excellent thermal conductivity. DETAILED DESCRIPTION
[0014] To achieve the above object, the present invention provides the following specific implementation methods and examples: A polyaromatic amide modified boron nitride-epoxy resin composite material, the preparation method of which comprises the following steps: (1) Adding sodium hydroxide solution and hexagonal nano boron nitride to a beaker for hydroxylation to obtain hydroxylated nano boron nitride, then adding the hydroxylated nano boron nitride to a hydrochloric acid solution, mixing evenly, adding elemental iron, and then adding 4-diazodiphenylamine sulfate, the mass ratio of hexagonal nano boron nitride to 4-diazodiphenylamine sulfate is 100:450-500, stirring to react, performing a diazonium salt reaction, the diazonium salt reaction temperature is 25-35°C, the diazonium salt reaction time is 30-90min, and obtaining surface amino-treated nano boron nitride; (2) Adding N-methylpyrrolidone to the reactor, then adding amino-modified nano-boron nitride and 3,5-diaminobenzoic acid, stirring and mixing evenly, ultrasonically dispersing, then adding a mixed solution of pyridine and triphenylphosphine, and then adding lithium chloride, the mass ratio of amino-modified nano-boron nitride, 3,5-diaminobenzoic acid, pyridine, triphenylphosphine and lithium chloride is 100:60-80:90-110:320-350:20-30, reacting in a nitrogen atmosphere, the reaction temperature is 120-150°C, the reaction time is 12-18h, after the reaction is completed, cooling, filtering, washing, and drying to obtain polyaromatic amide modified boron nitride; (3) Add acetone solvent to a beaker, then add polyaromatic amide modified boron nitride, disperse under ultrasonic stirring, then add epoxy resin, azodicarbonamide and diethylenetriamine, the mass ratio of polyaromatic amide modified boron nitride, epoxy resin, azodicarbonamide and diethylenetriamine is 15-25:100:2-8:1-3, stir and mix to react, the reaction temperature is 100-120°C, the reaction time is 6-12h. After the reaction is completed, evaporate the solvent in a water bath to obtain a polyaromatic amide modified boron nitride-epoxy resin composite material. Example
[0015] (1) Adding sodium hydroxide solution and hexagonal nano-boron nitride into a beaker for hydroxylation treatment to obtain hydroxylated nano-boron nitride, then adding the hydroxylated nano-boron nitride into a hydrochloric acid solution, mixing evenly, adding elemental iron, and then adding 4-diazodiphenylamine sulfate, the mass ratio of hexagonal nano-boron nitride to 4-diazodiphenylamine sulfate is 100:500, stirring to react, and performing a diazonium salt reaction. The diazonium salt reaction temperature is 25°C, and the diazonium salt reaction time is 30 minutes to obtain surface amino-treated nano-boron nitride; (2) Add N-methylpyrrolidone to the reactor, then add amino-modified nano-boron nitride and 3,5-diaminobenzoic acid, stir and mix evenly, disperse by ultrasonication, then add a mixed solution of pyridine and triphenylphosphine, and then add lithium chloride. The mass ratio of amino-modified nano-boron nitride, 3,5-diaminobenzoic acid, pyridine, triphenylphosphine and lithium chloride is 100:60:90:320:20. React in a nitrogen atmosphere at a reaction temperature of 120°C for a reaction time of 12 hours. After the reaction is completed, cool, filter, wash and dry to obtain polyaromatic amide modified boron nitride; (3) Add acetone solvent to a beaker, then add polyaromatic amide modified boron nitride, disperse under ultrasonic stirring, then add epoxy resin, azodicarbonamide and diethylenetriamine, the mass ratio of polyaromatic amide modified boron nitride, epoxy resin, azodicarbonamide and diethylenetriamine is 15:100:2:1, stir and mix to react, the reaction temperature is 100°C, and the reaction time is 6 hours. After the reaction is completed, evaporate the solvent in a water bath to obtain a polyaromatic amide modified boron nitride-epoxy resin composite material. Example
[0016] (1) Adding sodium hydroxide solution and hexagonal nano boron nitride into a beaker for hydroxylation treatment to obtain hydroxylated nano boron nitride, then adding the hydroxylated nano boron nitride into a hydrochloric acid solution, mixing evenly, adding elemental iron, and then adding 4-diazodiphenylamine sulfate, the mass ratio of hexagonal nano boron nitride to 4-diazodiphenylamine sulfate is 100:460, stirring to react, performing a diazonium salt reaction, the diazonium salt reaction temperature is 28°C, the diazonium salt reaction time is 40 minutes, and obtaining surface amino nano boron nitride; (2) Add N-methylpyrrolidone to the reactor, then add amino-modified nano-boron nitride and 3,5-diaminobenzoic acid, stir and mix evenly, disperse by ultrasonication, then add a mixed solution of pyridine and triphenylphosphine, then add lithium chloride, the mass ratio of amino-modified nano-boron nitride, 3,5-diaminobenzoic acid, pyridine, triphenylphosphine and lithium chloride is 100:65:95:330:24, react in a nitrogen atmosphere, the reaction temperature is 125°C, the reaction time is 14h, after the reaction is completed, cool, filter, wash and dry to obtain polyaromatic amide modified boron nitride; (3) Add acetone solvent to a beaker, then add polyaromatic amide modified boron nitride, disperse under ultrasonic stirring, then add epoxy resin, azodicarbonamide and diethylenetriamine, the mass ratio of polyaromatic amide modified boron nitride, epoxy resin, azodicarbonamide and diethylenetriamine is 16:100:4:1.5, stir and mix to react, the reaction temperature is 105°C, and the reaction time is 8 hours. After the reaction is completed, evaporate the solvent in a water bath to obtain a polyaromatic amide modified boron nitride-epoxy resin composite material. Example
[0017] (1) Adding sodium hydroxide solution and hexagonal nano boron nitride into a beaker for hydroxylation treatment to obtain hydroxylated nano boron nitride, then adding the hydroxylated nano boron nitride into a hydrochloric acid solution, mixing evenly, adding elemental iron, and then adding 4-diazodiphenylamine sulfate, the mass ratio of hexagonal nano boron nitride to 4-diazodiphenylamine sulfate is 100:480, stirring to react, performing a diazonium salt reaction, the diazonium salt reaction temperature is 30°C, the diazonium salt reaction time is 60 minutes, and obtaining surface amino nano boron nitride; (2) Add N-methylpyrrolidone to the reactor, then add amino-modified nano-boron nitride and 3,5-diaminobenzoic acid, stir and mix evenly, disperse by ultrasonication, then add a mixed solution of pyridine and triphenylphosphine, and then add lithium chloride. The mass ratio of amino-modified nano-boron nitride, 3,5-diaminobenzoic acid, pyridine, triphenylphosphine and lithium chloride is 100:70:100:340:26. React in a nitrogen atmosphere at a reaction temperature of 140°C for 16 hours. After the reaction is completed, cool, filter, wash and dry to obtain polyaromatic amide modified boron nitride; (3) Add acetone solvent to a beaker, then add polyaromatic amide modified boron nitride, disperse by ultrasonic stirring, then add epoxy resin, azodicarbonamide and diethylenetriamine, the mass ratio of polyaromatic amide modified boron nitride, epoxy resin, azodicarbonamide and diethylenetriamine is 24:100:6:2, stir and mix to react, the reaction temperature is 115°C, and the reaction time is 10 h. After the reaction is completed, evaporate the solvent in a water bath to obtain a polyaromatic amide modified boron nitride-epoxy resin composite material. Example
[0018] (1) Adding sodium hydroxide solution and hexagonal nano boron nitride into a beaker for hydroxylation treatment to obtain hydroxylated nano boron nitride, then adding the hydroxylated nano boron nitride into a hydrochloric acid solution, mixing evenly, adding elemental iron, and then adding 4-diazodiphenylamine sulfate, the mass ratio of hexagonal nano boron nitride to 4-diazodiphenylamine sulfate is 100:490, stirring to react, and performing a diazonium salt reaction. The temperature of the diazonium salt reaction is 32°C, and the time of the diazonium salt reaction is 85 minutes to obtain surface amino nano boron nitride; (2) Add N-methylpyrrolidone to the reactor, then add amino-modified nano-boron nitride and 3,5-diaminobenzoic acid, stir and mix evenly, disperse by ultrasonication, then add a mixed solution of pyridine and triphenylphosphine, and then add lithium chloride. The mass ratio of amino-modified nano-boron nitride, 3,5-diaminobenzoic acid, pyridine, triphenylphosphine and lithium chloride is 100:75:105:345:28. React in a nitrogen atmosphere at a reaction temperature of 145°C for 16 hours. After the reaction is completed, cool, filter, wash and dry to obtain polyaromatic amide modified boron nitride; (3) Add acetone solvent to a beaker, then add polyaromatic amide modified boron nitride, disperse under ultrasonic stirring, then add epoxy resin, azodicarbonamide and diethylenetriamine, the mass ratio of polyaromatic amide modified boron nitride, epoxy resin, azodicarbonamide and diethylenetriamine is 24:100:7:2.5, stir and mix to react, the reaction temperature is 118°C, and the reaction time is 10 h. After the reaction is completed, evaporate the solvent in a water bath to obtain a polyaromatic amide modified boron nitride-epoxy resin composite material. Example
[0019] (1) Adding sodium hydroxide solution and hexagonal nano-boron nitride into a beaker for hydroxylation treatment to obtain hydroxylated nano-boron nitride, then adding the hydroxylated nano-boron nitride into a hydrochloric acid solution, mixing evenly, adding elemental iron, and then adding 4-diazodiphenylamine sulfate, the mass ratio of hexagonal nano-boron nitride to 4-diazodiphenylamine sulfate is 100:500, stirring to react, and performing a diazonium salt reaction. The diazonium salt reaction temperature is 35°C, and the diazonium salt reaction time is 90 minutes to obtain surface amino-treated nano-boron nitride; (2) Add N-methylpyrrolidone to the reactor, then add amino-modified nano-boron nitride and 3,5-diaminobenzoic acid, stir and mix evenly, disperse by ultrasonication, then add a mixed solution of pyridine and triphenylphosphine, and then add lithium chloride. The mass ratio of amino-modified nano-boron nitride, 3,5-diaminobenzoic acid, pyridine, triphenylphosphine and lithium chloride is 100:80:110:350:30. React in a nitrogen atmosphere at a reaction temperature of 150°C for 18 hours. After the reaction is completed, cool, filter, wash and dry to obtain polyaromatic amide modified boron nitride; (3) Add acetone solvent to a beaker, then add polyaromatic amide modified boron nitride, disperse under ultrasonic stirring, then add epoxy resin, azodicarbonamide and diethylenetriamine, the mass ratio of polyaromatic amide modified boron nitride, epoxy resin, azodicarbonamide and diethylenetriamine is 25:100:8:3, stir and mix to react, the reaction temperature is 120°C, and the reaction time is 12 h. After the reaction is completed, evaporate the solvent in a water bath to obtain a polyaromatic amide modified boron nitride-epoxy resin composite material.
[0020] Comparative Example 1 (1) Adding sodium hydroxide solution and hexagonal nano boron nitride into a beaker for hydroxylation treatment to obtain hydroxylated nano boron nitride, then adding hydroxylated nano boron nitride into hydrochloric acid solution, adding elemental iron after mixing evenly, and then adding 4-diazodiphenylamine sulfate, the mass ratio of hexagonal nano boron nitride to 4-diazodiphenylamine sulfate is 100:350, stirring to react, performing diazonium salt reaction, the diazonium salt reaction temperature is 30°C, the diazonium salt reaction time is 60min, and obtaining surface amino nano boron nitride; (2) Add N-methylpyrrolidone to the reactor, then add amino-modified nano-boron nitride and 3,5-diaminobenzoic acid, stir and mix evenly, disperse by ultrasonication, then add a mixed solution of pyridine and triphenylphosphine, and then add lithium chloride. The mass ratio of amino-modified nano-boron nitride, 3,5-diaminobenzoic acid, pyridine, triphenylphosphine and lithium chloride is 100:30:45:150:10. React in a nitrogen atmosphere at a reaction temperature of 140°C for 15 hours. After the reaction is completed, cool, filter, wash and dry to obtain polyaromatic amide modified boron nitride; (3) Add acetone solvent to a beaker, then add polyaromatic amide modified boron nitride, disperse under ultrasonic stirring, then add epoxy resin, azodicarbonamide and diethylenetriamine, the mass ratio of polyaromatic amide modified boron nitride, epoxy resin, azodicarbonamide and diethylenetriamine is 8:100:1:0.5, stir and mix to react, the reaction temperature is 110°C, and the reaction time is 8 hours. After the reaction is completed, evaporate the solvent in a water bath to obtain a polyaromatic amide modified boron nitride-epoxy resin composite material.
[0021] 0.5 g of the polyaromatic amide modified boron nitride-epoxy resin composite material prepared during the experiment was taken and the corresponding thermal conductivity was tested using a 2500S thermal conductivity meter.
[0022] project Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Thermal conductivity (W / m·k) 0.419 0.710 1.051 0.856 0.571 0.308 0.5 g of the polyaromatic amide modified boron nitride-epoxy resin composite material prepared during the experiment was taken and the electrical strength was tested using a M352733 voltage breakdown tester.
[0023] project Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Electrical strength (kV / mm) 32.27 36.12 35.08 33.87 31.79 28.14
Claims
1. A polyaromatic amide modified boron nitride-epoxy resin composite material, characterized in that: The preparation method of the polyaromatic amide modified boron nitride-epoxy resin composite material comprises the following steps: (1) adding sodium hydroxide solution and hexagonal nano-boron nitride into a beaker for hydroxylation to obtain hydroxylated nano-boron nitride, then adding the hydroxylated nano-boron nitride into a hydrochloric acid solution, mixing evenly, adding elemental iron, and then adding 4-diazodiphenylamine sulfate, stirring and reacting, performing a diazonium salt reaction, and obtaining surface amino-treated nano-boron nitride; (2) Adding N-methylpyrrolidone to the reactor, then adding amino-modified nano boron nitride and 3,5-diaminobenzoic acid, stirring and mixing evenly, ultrasonically dispersing, then adding a mixed solution of pyridine and triphenylphosphine, and then adding lithium chloride, reacting in a nitrogen atmosphere, and after the reaction is completed, cooling, filtering, washing, and drying to obtain polyaromatic amide modified boron nitride; (3) Add acetone solvent to a beaker, then add polyaromatic amide modified boron nitride, disperse by ultrasonic stirring, then add epoxy resin, azodicarbonamide and diethylenetriamine, stir and react. After the reaction is completed, evaporate the solvent in a water bath to obtain a polyaromatic amide modified boron nitride-epoxy resin composite material.
2. The polyaromatic amide modified boron nitride-epoxy resin composite material according to claim 1, characterized in that: In the step (1), the mass ratio of hexagonal nano boron nitride to 4-diazodiphenylamine sulfate is 100:450-500.
3. The polyaromatic amide modified boron nitride-epoxy resin composite material according to claim 1, characterized in that: The temperature of the diazonium salt reaction in step (1) is 25-35° C., and the time of the diazonium salt reaction is 30-90 min.
4. The polyaromatic amide modified boron nitride-epoxy resin composite material according to claim 1, characterized in that: In the step (2), the mass ratio of the amino-modified nano-boron nitride, 3,5-diaminobenzoic acid, pyridine, triphenylphosphine and lithium chloride is 100:60-80:90-110:320-350:20-30.
5. The polyaromatic amide modified boron nitride-epoxy resin composite material according to claim 1, characterized in that: The reaction temperature in the nitrogen atmosphere in step (2) is 120-150° C., and the reaction time in the nitrogen atmosphere is 12-18 hours.
6. The polyaromatic amide modified boron nitride-epoxy resin composite material according to claim 1, characterized in that: In the step (3), the mass ratio of polyaromatic amide modified boron nitride, epoxy resin, azodicarbonamide and diethylenetriamine is 15-25:100:2-8:1-3.
7. The polyaromatic amide modified boron nitride-epoxy resin composite material according to claim 1, characterized in that: The stirring and mixing reaction temperature in step (3) is 100-120° C., and the reaction time is 6-12 hours.
Citation Information
Cited By
Hyperbranched boron nitride-loaded cellulose composite membrane as well as preparation method and application thereof
CN120718349A